Implementing competency based admissions at the Albert Einstein College of Medicine. Issue 1 (1st January 2016) - Kerrigan, Noreen; Akabas, Myles H.; Betzler, Thomas F.; Castaldi, Maria; Kelly, Mary S.; Levy, Adam S.; Reichgott, Michael J.; Ruberman, Louise; Dolan, Siobhan M.
Abstract : The Albert Einstein College of Medicine (Einstein) was founded in 1955 during an era of limited access to medical school for women, racial minorities, and many religious and ethnic groups. Located in the Bronx, NY, Einstein seeks to educate physicians in an environment of state-of-the-art scientific inquiry while simultaneously fulfilling a deep commitment to serve its community by providing the highest quality clinical care. A founding principle of Einstein, the basis upon which Professor Einstein agreed to allow the use of his name, was that admission to the student body would be based entirely on merit. To accomplish this, Einstein has long used a 'holistic' approach to the evaluation of its applicants, actively seeking a diverse student body. More recently, in order to improve its ability to identify students with the potential to be outstanding physicians, who will both advance medical knowledge and serve the pressing health needs of a diverse community, the Committee on Admissions reexamined and restructured the requirements for admission. These have now been categorized as four 'Admissions Competencies' that an applicant must demonstrate. They include: 1) cocurricular activities and relevant experiences; 2) communication skills; 3) personal and professional development; and 4) knowledge. The purpose of this article is to describe the process that resulted in the introduction and implementation of this competency based approach to the admission process.